SPECIES COMPOSITION OF ANIMALS INTERNAL ORGANS MICROFLORA IN ASSOCIATED EXPERIMENTAL INFECTION - Сахаров, Сергей Павлович; Молокова, Ольга Александровна; Фролова, Ольга Игоревна (Medicine in Kuzbass, 2021)
Objective. In recent years, an increase in the incidence of infectious diseases caused by bacterial associations has been noted. The change in the species composition of microorganisms in associations requires studying the mechanisms of interaction of pathogens, identifying the role of associated microflora during the infectious process. The purpose of the research is to study the pathomorphology of the animals organs infected with P. aeruginosa and S. aureus in cultivated and non-cultivated forms; determine the microbial landscape of blood and internal organs; identify the biochemical characteristics of microorganisms. Methods. The experiment was carried out on 58 rabbits, divided into 3 groups. The animals were infected with cultivated and non-cultivated forms of P. aeruginosa and S. aureus bacteria isolated from patients treated in the burn department of the Regional Clinical Hospital N 1 in Tyumen. Species identification of bacteria in dead animals in blood, liver, lungs and kidneys was carried out with a study of their biochemical properties. Results. It was revealed that the death of animals on the 8-9th day developed due to DAP of the lungs and discirculatory – destructive changes in the parenchymal organs. On the 11-12th day, the second peak of mortality was noted, due to the progression of systemic inflammation. In group II, on the 2-5th day, the fulminant course of the disease led to massive death of animals due to the inclusion of E. coli in the association. The second peak of mortality on the 8th day of the disease is due to systemic inflammation and progressive multiple organ failure.Conclusions. When animals are infected with the association of P. aeruginosa and S. aureus in an uncultivated state, they are reversed to an uncultivated state. The liver is a reservoir of infectious origin in a generalized infectious process. The translocated E. coli acquired atypical properties that enhance its virulence. In a cultivated form, translocated E. coli can exist as a monoculture or in association with P. aeruginosa and S. aureus, contributing to a more severe course of the infectious process due to a synergistic effect.